Karakteristik Tafsir Tarjuman Al-Mustafid - Suarni Suarni (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
Abstract: Tarjuman Tafsir al-Mustafid is one of the Quran interpretations written in Arab Jawi (an old Malay-style writing) which is considered as the earliest and the most complete Quran interpretation in Indonesia. This interpretation was written by Sheikh Abdur Rauf al-Singkili, during the reign of Queen Safiyatuddin. There are two views about the writing source of this interpretation, first as the translation of a Baidhawi interpretation and second as the translation of Jalalain and Al-Khazin books. The method applied in the writing of this interpretation can be analyzed from its interpretation and meaning. In term of its interpretation, this book used tahlili (analysis) as it explains the verses in sequence and their content from various aspects, while in term of its meaning it used ijmali (global) as its explanation is in accordance with the meaning of the verses it describes.Abstrak: Tafsir Tarjuman al-Mustafid adalah salah satu tafsir yang berbahasa Arab Jawi (Melayu) yang dianggap sebagai tafsir paling awal dan lengkap di Nusantara. Tafsir ini ditulis oleh Syekh Abdur Rauf al-Singkili, pada masa pemerintahan Ratu Safiyatuddin. Ada dua pandangan mengenai sumber penulisan tafsir ini adalah pertama sebagai terjemahan dari tafsir Baidhawi, kedua sebagai terjemahan dari kitab Jalalain dan Al-Khazin. Metode yang diterapkan dalam penulisan tafsir ini adalah dapat ditinjau dari sudut penafsiran dan makna. Dari sudut cara penafsiran adalah tahlili (analisis) karena menjelaskan ayat secara berurutan dan kandungan ayat dari berbagai aspek. Sedangkan ijmali (global) adalah karena menjelaskan maknanya sesuai dengan arti ayat yang dijelaskan.